Arthritis in sarcoidosis: A multicentric study from India. (5th September 2018) - ,; Agarwal, Vikas; Agrawal, Vinita; Aggarwal, Amita; Aggarwal, Parshant; Chowdhury, Abhra C.; Ghosh, Parasar; Jain, Avinash; Lawrence, Able; Misra, Durga P.; Misra, Ramnath; Mohapatra, Madhusmita M.; et al.
Abstract: Introduction: Ten to 15% of patients with sarcoidosis have associated arthritis. Chronic arthritis is fairly uncommon. There is a paucity of data on articular manifestations of the disease from India. Methods: Case records of adult patients with sarcoidosis presenting to 11 rheumatology centers from 2005 to 2017 were retrospectively reviewed. Joint involvement was assessed clinically, classified as acute or chronic depending on duration of symptoms less or greater than 6 months, respectively. Results: A total of 117 patients with sarcoid arthritis were reviewed. Forty‐five patients were classified as having Lofgren's syndrome. The pattern of joint involvement revealed the ankle to be most commonly affected in both the groups. Shoulder, wrist, metacarpophalangeal, proximal interphalangeal joints of hands and knee joint involvement were significantly more common in chronic sarcoid arthritis. Peripheral lymphadenopathy and uveitis were significantly more frequent in chronic sarcoid arthritis. Forty out of 49 patients with acute arthritis followed up over a median of 1.8 years had achieved complete remission. Twelve out of 16 chronic sarcoid arthritis (median follow up 2.5 years) had achieved complete remission with 15, 12 and five patients on steroids, methotrexate and hydroxychloroquine, respectively. One patient with acute sarcoid arthritis with concomitant interstitial lung disease had died due to lung infection. Conclusion: Acute oligoarthritis was the commonest presentation with the ankle being the most commonly affected joint. Upper limb joint (predominantly distal) and knee involvement were more common as reported in our largest series worldwide of chronic sarcoid arthritis in adults. Hilar adenopathy and erythema nodosum were common extra‐articular features in both acute and chronic sarcoid arthritis. A limitation of the study was the retrospective nature of the analysis.